Morphologies and material properties of ZnO nanotubes, ZnO/ZnS core-shell nanorods, and ZnO/ZnS core-shell nanotubes. Issue 5 (1st March 2022) - Tsai, Yu-Sheng; Chen, Jyun-Rong; Lee, Chang-Hsueh; Kuo, Chih-Chen; Lin, Ya-Hsuan; Wang, Chun-Chieh; Chang, Yu-Cheng; Wu, YewChung Sermon; Chen, Hsiang
Abstract: In this study, ZnO nanotubes, ZnO/ZnS core-shell nanorods, and ZnO/ZnS nanotubes were fabricated. To fabricate different types of ZnO-based nanocomposites, the central area of the ZnO nanorods was etched by a KCl solution and the outward shell was sulfurized to form ZnS/ZnO shell structures. Surface morphologies and material properties of the various nanostructures were examined by Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), and Transmission X-ray Microscopy (TXM). Multiple material characterizations including X-Ray Diffraction (XRD), X-Ray Photoelectron Spectroscopy (XPS), and Photoluminescence (PL) were performed. Results indicate that larger surface areas and higher defect concentrations can be obtained by the etching of ZnO nanorods. ZnO/ZnS nanotubes formed by sulfurization roughen the shell surface and mitigate defects. Results indicate that ZnO and ZnO/ZnS nanotubes show promise for future sensing device applications.